Information in action : - Killingsworth, M. Jimmie (Allyn and Bacon, 1996)
Process-oriented approach with an emphasis on audience and contexts and a social-rhetorical base. More on the context (i.e., social, cultural, and ethical issues) than other texts. Innovative CORE method teaches how to write an action-oriented document based on user needs. New reorganization enhances teachability of the writing process and the CORE method. New: electronic communication integrated; inclusion of topics such as international and intercultural communication and diversity; 4-color graphics.